Knowledge, attitude and practices regarding generic medicines and its usage: a community-based study - Ballala, Kirthinath; Rao, Chythra R.; Chaudhary, Aparna S.; Bidnurmath, Ashwini S.; Pandey, Akhilesh K. (International Journal Of Community Medicine And Public Health, 2019)
Background: India is the largest provider of generic medications globally. Despite this, several essential medicines remain inaccessible to majority of the general population, due to poor awareness, unavailability of drugs, distrust about the quality of the medicines, poor policy implementation and inadequate recommendation by doctors. Methods: A community-based cross-sectional study was carried out among 1151 adults in rural and urban areas attached to the community outreach area of a University Medical College. Written informed consent was taken from the participants. Data was collected using a pre-tested semi-structured online questionnaire and analysed using SPSS 15.0. Results: Knowledge regarding generic medicines was found to be low among the surveyed population (666, 57.9%), irrespective of their socio-economic status, education, occupation, place of residence or presence of chronic illnesses. As the knowledge was poor, participants were briefed about the generic medicines and their benefits. Thereafter, the attitude was assessed and found to be favourable among more than half (633, 55.0%) of the surveyed population. The usage of Generic medicines was found to be poor among the respondents. Only 53 (4.6%) of the total study population had switched from branded to generic medicines in the past six months as generic medicines were less expensive compared to their branded counterparts. Conclusions: The awareness about generic drugs and its usage was poor in the surveyed population. A favourable attitude towards generic drugs was achieved by educating the people about their similarity to branded medications. Therefore, there is a need to educate people not only about the quality, safety and efficacy of the generic medicines but also about the government initiatives like the Jan Aushadhi scheme.